Unraveling the complex relationship between prenatal alcohol exposure, hippocampal LTP, and learning and memory - Goncalves-Garcia, Monica; Hamilton, Derek Alexander (Frontiers in Molecular Neuroscience, 2024)
Prenatal alcohol exposure (PAE) has been extensively studied for its profound impact on neurodevelopment, synaptic plasticity, and cognitive outcomes. While PAE, particularly at moderate levels, has long-lasting cognitive implications for the exposed individuals, there remains a substantial gap in our understanding of the precise mechanisms underlying these deficits. This review provides a framework for comprehending the neurobiological basis of learning and memory processes that are negatively impacted by PAE. Sex differences, diverse PAE protocols, and the timing of exposure are explored as potential variables influencing the diverse outcomes of PAE on long-term potentiation (LTP). Additionally, potential interventions, both pharmacological and non-pharmacological, are reviewed, offering promising avenues for mitigating the detrimental effects of PAE on cognitive processes. While significant progress has been made, further research is required to enhance our understanding of how prenatal alcohol exposure affects neural plasticity and cognitive functions and to develop effective therapeutic interventions for those impacted. Ultimately, this work aims to advance the comprehension of the consequences of PAE on the brain and cognitive functions.